2015
DOI: 10.1097/md.0000000000002244
|View full text |Cite
|
Sign up to set email alerts
|

Down-Regulated Phosphoglycerate Kinase 1 Expression Is Associated With Poor Prognosis in Patients With Gallbladder Cancer

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 36 publications
1
7
0
Order By: Relevance
“…Here, significant associations between high PGK1 expression and FIGO stage, histological grade, pathological type, and lymph node metastasis were identified. Similar to a report on gallbladder cancer [ 28 ], we further demonstrated that high PGK1 expression was associated with poor prognosis in endometrial carcinoma patients.…”
Section: Discussionsupporting
confidence: 90%
“…Here, significant associations between high PGK1 expression and FIGO stage, histological grade, pathological type, and lymph node metastasis were identified. Similar to a report on gallbladder cancer [ 28 ], we further demonstrated that high PGK1 expression was associated with poor prognosis in endometrial carcinoma patients.…”
Section: Discussionsupporting
confidence: 90%
“…Hu et al ( 2017 ) found that PGK1 was overexpressed in liver cancer cells and that PGK1 acetylation promoted its enzyme activity and cancer cell metabolism. Additionally, PGK1 is also abnormally expressed in a great deal of cancers, such as gallbladder cancer (Lu et al, 2015 ), astrocytoma (Yan et al, 2012 ), gastric cancer (Zieker et al, 2010a , b ), and pancreatic ductal adenocarcinoma (Hwang et al, 2006 ), and it is closely correlated to tumor occurrence, metastasis, and invasion. Moreover, PKG1 can also be used as a target gene of miRNAs to modulate tumor development and progression.…”
Section: Discussionmentioning
confidence: 99%
“…PGK1 is a ubiquitous enzyme in all somatic cells and PGK2 is preferentially expressed in the testis 10 . Notably, PGK1, which is highly conserved from rabbits to humans and is a well-studied isozyme of the PGK family, has been reported to be upregulated in various types of tumor cells, such as colorectal cancer 11 , 12 , breast 4 , hepatocellular carcinoma 13 , gallbladder cancer 14 , and lung cancer. In addition, dysfunction of the PGK family involves metabolic programming and the Warburg effect in tumorigenesis 15 .…”
Section: Introductionmentioning
confidence: 99%